The Millennial Mindset: Unraveling Fact from Fiction - Luttrell, Regina; McGrath, Karen (Rowman & Littlefield Publishers, 2016)
We’ve all heard that Millennials are smarter than everyone else, unique in every way possible, that they have probably been millionaires since age seven, and that they are poised to take over the world. We’ve also heard that they are lazy, unmotivated, entitled, and condescending know-it-alls. How can this generation have such opposing characteristics? What is the truth about this generation? The Millennial Mindset offers parents, educators, managers, and co-workers insights and suggestions on how to engage, prepare, and foster the Millennial generation in all aspects of life. Through interviews with millennials and those who work with or otherwise engage them, Regina Luttrell and Karen McGrath offer ways for Millennials to better understand older generations and their peers so they can coexist without animosity in today’s fast-paced globalized world. They also offer insight into Millennial characteristics, passions, and goals for those who work with, live with, or otherwise co-exist with Millennials. Readers will gain a better sense of what this generation has in store for the world, and how the world can best respond.